MoS2/MoOx‐Nanostructure‐Decorated Activated Carbon Cloth for Enhanced Supercapacitor Performance. Issue 5 (16th February 2018) - Sari, Fitri Nur Indah; Ting, Jyh‐Ming
Abstract: MoS2 /MoO x nanostructures were grown on activated carbon cloth through a facile one‐step microwave‐assisted hydrothermal method. The growth of MoS2 /MoO x on activated carbon cloth creates a unique structure that favors ion intercalation. The conductive activated carbon cloth, MoO3− x, and monoclinic MoO2 provide fast electron transport, whereas the MoS2 nanosheets/MoO3− x nanoparticles structure improves the capacitance. As a result, MoS2 /MoO x ‐nanostructure‐decorated activated carbon cloth shows a high specific capacitance of 230 F g −1 at a scan rate of 5 mV s −1 with a low contact resistance of approximately 1.91 Ω. Moreover, the activated carbon cloth acts as a template for the growth of a perpendicular MoS2 layer, which gives an excellent utilization rate of the active MoS2 /MoO x material. We also demonstrate that the MoS2 /MoO x /activated carbon cloth nanocomposite shows excellent electrochemical stability with retention up to 128 % after 1500 cycles. Finally, we show the use of a microwave‐assisted hydrothermal method for the synthesis of the MoS2 /MoO x /activated carbon cloth nanocomposite as an alternative and clean route to improve the kinetics of the intercalation redox reaction. Abstract : Of the same cloth : MoS2 /MoO x /activated carbon cloth (ACC) nanocomposites exhibit unique structures that favor ion intercalation and fast transport of electrons. A synergistic effect of MoS2, MoO3, MoO2, and ACC is also demonstrated. The resulting supercapacitor has an excellent utilization rate of the active MoS2 /MoO x material, as high as 914 F g −1 at 5 mV s −1, and excellent electrochemical stability with retention of up to 128 % after 1500 cycles at 200 mV s −1 .